Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. 4 . 102 - 52 + 4 . 10 + 1
= 4 . 100 - 25 + 4 . 10 + 1
= 400 - 25 + 40 + 1
= 416
b. 932 - 62 - 2 . 6 - 2
= 8649 - 36 - 12 - 2
= 8599
a: Ta có: \(4x^2-y^2+4x+1\)
\(=\left(2x+1\right)^2-y^2\)
\(=\left(2x+y-1\right)\left(2x-y-1\right)\)
\(=\left(20+5-1\right)\left(20-5-1\right)\)
\(=24\cdot14=336\)
\(x^2-y^2-2y-1\)
\(=x^2-\left(y+1\right)^2\)
\(=\left(x-y-1\right)\left(x+y+1\right)\)
\(=100\cdot\left(93-6-1\right)\)
=8600
a: Khi x=2 và y=-3 thì \(x^2+2y=2^2+2\cdot\left(-3\right)=4-6=-2\)
b: \(A=x^2+2xy+y^2=\left(x+y\right)^2\)
Khi x=4 và y=6 thì \(A=\left(4+6\right)^2=10^2=100\)
c: \(P=x^2-4xy+4y^2=\left(x-2y\right)^2\)
Khi x=1 và y=1/2 thì \(P=\left(1-2\cdot\dfrac{1}{2}\right)^2=\left(1-1\right)^2=0\)
\(Q=x^2-y^2-2y-1\)
\(\Rightarrow Q=x^2-\left(y^2+2y+1\right)\)
\(\Rightarrow Q=x^2-\left(y+1\right)^2\)
\(\Rightarrow Q=\left(x-y-1\right)\left(x+y+1\right)\)
Thay \(x=93;y=6\)vào \(Q\)ta được :
\(Q=\left(93-6-1\right)\left(93+6+1\right)\)
\(\Rightarrow Q=86.100\)
\(\Rightarrow Q=8600\)
Vậy \(Q=8600\)
Đề là gì thế bạn ?
\(x^2-y^2+2xy-1\)
\(=\left(x-y\right)^2-1\)
\(=\left(x-y-1\right)\left(x-y+1\right)\)
\(=\left(93-6-1\right)\left(93-6+1\right)\)
\(=86\cdot88=7568\)